Eating and Taking Photos: The Consumption of Food, Visual Representations and Gender. Mar del Plata (Argentina), 1930–1970 - Débora Garazi (Genre & Histoire)
In this article, I examine experiences of consumption and social interaction in establishments specialising in making, serving and selling food and beverages (such as restaurants, cafés, or tearooms) in Mar del Plata, Argentina, between the 1930s and 1970s. The ways that different social groups visited these places and consumed the products and services they offered varied at different historical moments. Gender, class and age were central in defining who was entitled to do so at any given time. Based on my analysis of more than 450 photographs, I argue that eating (by which I mean the experience of visiting dining establishments and consuming food there) and taking photos while doing so were part of a process of constructing status and individual and collective class and gender identities. Not only did these photographs constitute material evidence that certain people had visited these places, they also produced specific meanings. To construct the universe of meaning in which these photographs are embedded, I have also drawn on other sources such as advertisements, menus and newspaper articles.